الوسائط المتعددة في تعليم اللغة العربية - Mohammad Ahsanuddin; Hanem Elhusseini Ahmad Mohamed Saleh; Nuriyatul Hidayah (Prosiding Konferensi Nasional Bahasa Arab, 2020)
مستخلص البحثولقد شهد العالم في الربع الأخير من القرن العشرين سرعة مدهشة في حجم التغيرات التي انتشرت في كل مجال. وإذا كانت العولمة حتمية اقتضتها التحولات في كل مجال، فلابد للغة العربية من التكيف مع هذا الوضع العالمي الجديد لتتمكن من المشاركة الفعالة في التطور الاجتماعي، ولتحقيق ذلك لابد من تنمية الفكر العلمي وتجديد وسائل التعليم من خلال استخدام الوسائل المتعددة. تعتبر المدارس من أهم المؤسسات التي تحتاج إلى استخدام الوسائط المتعددة وذلك للمساعدة في توصيل المعلومات بدقة وعمق أكبر، وبالتالي تؤدي إلى رفع الكفاءة ومستوى الأداء. ،ومما لاشك فيه أن الوسائط المتعددة أصبحت جزءا لا يتجزأ من العملية التعليمية اليوم.الكلمات الرئيسية : الوسائط المتعددة، التعليم، اللغة العربية.AbstractIn the last quarter of the twentieth century, the world witnessed an amazing speed in the volume of changes that spread in every field. If globalization is an imperative necessitated by transformations in every field, then the Arabic language must adapt to this new global situation in order to be able to participate effectively in social development, and to achieve this must develop scientific thought and renew learning methods through the use of multiple means. Schools are considered one of the most important institutions that require the use of multimedia in order to help communicate information with greater accuracy and depth, and thus increase efficiency and level of performance. And, undoubtedly, multimedia has become an integral part of the educational process today.Keyword : Multimedia, Learning, Arabic Language.